Students were asked to solve the equation y=x−ab for a. Their work is shown below.



Student 1:

y=x−ab

by=x−a

by−x=a



Student 2:

y=x−ab

yb=x−a

yb−x=−a

−yb+x=a



Student 3:

y=x−ab

by=x−a

by−x=−a

−by+x=a



Which student solved the equation correctly? Justify your answer by explaining why the other two students solved the equation incorrectly.

1 answer

Student 3 solved the equation correctly.

Student 1 made a mistake by incorrectly subtracting "a" from both sides of the equation, resulting in the equation "by - x = a" instead of "by - x = -a".

Student 2 also made a mistake by incorrectly dividing both sides of the equation by "b", resulting in the equation "-yb + x = a" instead of "-yb + x = -a".

Student 3, on the other hand, correctly subtracted "a" from both sides of the equation and obtained the correct equation "-by + x = a".